Molecular insights into STAT1a protein in rohu (Labeo rohita): unveiling expression profiles, SRC homology domain recognition, and protein-protein interactions triggered by poly I: C - Das, Basanta Kumar; Panda, Soumya Prasad; Pradhan, Smruti Priyambada; Raut, Subhashree Subhasmita; Kumari, Mala; Meena, Dharmendra Kumar (Frontiers in Immunology, 2024)
Signal Transducer and Activator of Transcription (STAT1a) is an essential signal transduction protein involved in the interferon pathway. A vital part of interferon (IFN)-alpha/beta and gamma signaling is STAT1a. Although seven isoforms of STAT protein have been described in humans, limited information is known about the STAT protein in fish, and no information is available in Indian major carps (IMC). STAT1a plays an essential part of the innate immune response. The full-length CDS of Labeo rohita STAT1a (LrSTAT1a) transcript consisted of 3238 bp that encoded a polypeptide of 721 amino acids sequence was identified. Phylogenetic analyses were performed based on the nucleotide sequences. Based on our findings, other vertebrates share a high degree of conservation with STAT1a. Additionally, we report that the in vivo immune stimulant poly I: C treatment of various tissues resulted in the expression of LrSTAT1a as determined by quantitative real-time polymerase chain reaction (qRT-PCR). In the current investigation, treatment with poly I: C dramatically increased the expression of LrSTAT1a in nearly every organ and tissue, with the brain, muscle, kidney, and intestine showing the highest levels of expression compared to the control. We made a 3D model of the STAT1a protein by using close structure homologs that were already available in the database.. The model was then checked using molecular dynamics (MD) simulations. Consistent with previous research, the MD study highlighted the significance of the STAT1a protein, which is responsible for Src homology 2 (SH2) recognition. An important Hbonding that successfully retains SH2 inside the STAT1a binding cavity was determined to be formed by the conserved residues SER107, GLN530, SER583, LYS584, MET103, and ALA106.According to this study, the immunological response in L. rohita is mediated by STAT1a.